COMPARISON OF POSITIVE ASPIRATION DURING INFERIOR ALVEOLAR NERVE BLOCK USING CONVENTIONAL METALLIC DENTAL SYRINGE VS. DISPOSABLE PLASTIC SYRINGE - Mazhar, Bushra; Younus, Shoaib; Akhtar, Uzair Bin; Altaf, Ali; Javed, Farhan; Sajid, Malik Ali Hassan (Pakistan Armed Forces Medical Journal, 2020)
Objective: To compare the frequency of positive aspiration during inferior alveolar nerve blocks using conventional metallic dental syringe and disposable 3cc plastic syringe and to observe the efficacy of aspiration of both syringe systems.Study Design: Comparative prospective study.Place and Duration of Study: Oral and Maxillofacial Surgery Department, Institute of Dentistry, CMH Lahore Medical College, from May 2019 to Jul 2019.Methodology: One hundred patients requiring administration of inferior alveolar nerve block for mandibular oral surgery procedures were selected on the basis of consecutive convenience sampling. Inclusion criteria was patients undergoing oral surgery procedures of mandible. Two groups were made. 1st patient was allotted to group A by coin-toss method. Every alternate patient was included in group B. Group A was administered inferior alveolar nerve block using conventional metallic dental syringe while for group B, 3cc disposable hypodermic plastic syringe was used. A single operator administered all inferior alveolar nerve blocks. Frequency of positive aspiration was noted down for each group.Results: Forty six (46%) subjects were males and 54 (54%) were females. Mean age was 35.9 ± 13.7 years. Frequency of positive aspiration in the metallic syringe group was 15 (15%) and in the disposable syringe group was 8 (8%). Using Pearson chi square test, no statistically significant difference was found between aspiration frequency of the two groups (p=0.09).Conclusion: The statistically insignificant difference between the aspiration rates of both syringes implies that neither of the systems is superior to the other in aspiration.